Parliaments and the Political Nation 1559-1640 - Croft, Pauline (Czasopismo Prawno-Historyczne, 1989)
Over the last fifteen years the history of the English parliament in this period has been largely transformed, both by the application of new research and by the challenging of old assumptions. What had seemed a settled, indeed virtually exhausted topic, its clear outlines and high points universally accepted, has become instead something of a minefield in which it is wise to tread with extreme caution. On the whole, the new interpretations which have emerged are better established for the reign of Elizabeth (1558 - 1603) than for the early seventeenth century, so this paper will tackle the two periods separately, although many of the themes inevitably overlap.